Peranan Hakim Sebagai Mediator Dalam Penyelesaian Perkara Wanprestasi Perjanjian Kerjasama Investasi Tanah Melalui Mediasi Di Pengadilan Negeri Malang Kelas IA - Fauziyah Salsabila Alfiani Putri, Ni'matul; Mara Ditta Caesar Purwanto, Aldira (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Mediation is a mechanism for resolving civil disputes through a negotiation process facilitated by a mediator to reach an amicable agreement between the parties. In the Indonesian legal system, mediation has become an integral part of the civil justice process as a mandatory stage prior to litigation. This study aims to analyse the role of judges as mediators in breach of contract cases, identify the obstacles encountered, and the efforts made in the mediation process. The type of research used is empirical legal research, with data obtained through interviews with judges and deputy court clerks as well as direct observation at the Malang Class IA District Court. The results of the study show that the role of judges as mediators is very significant in encouraging the peaceful resolution of disputes. This is evidenced by case study No. 59/Pdt.G/2024/PN Mlg, in which mediation successfully resulted in a peaceful agreement as outlined in a settlement deed. The main obstacles faced include low legal awareness and a lack of good faith on the part of the parties. To overcome this, judges implemented strategies such as encouraging open communication, using an empathetic approach, and utilising the professionalism of certified mediators.